Adhesive composition, UV anti-viscosity adhesive and UV anti-viscosity film
By using a UV mucosa reducing film containing a adhesive composition containing a cured resin, a reactive diluent and a photosensitive monomer, the problems of insufficient adhesion and serious glue leakage in the prior art are solved, and a higher Process yield and better bonding performance.
Patent Information
- Application Number
- CN202111675770.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-12-31
AI Technical Summary
The existing UV mucosa is insufficiently adhered when cutting flexible panels or large-angle irregular-shaped materials, which easily overflows glue and affects the process yield.
A viscose composition is adopted, including 18 to 50 wt% curing resin, 40 to 80 wt% reactive diluent, 0.01 to 5 wt% photoinitiator, 0.01 to 5 wt% curing agent and 0.01 to 40 wt% solvent. The curing resin is a non-photosensitive resin, and the active diluent includes a photosensitive monomer. By adjusting the component ratio and type, the cross-linking density, hardness and viscosity of the UV viscosity reducing glue are improved.
It reduces the chance of glue spilling, reduces the difficulty of peeling during the process, improves the process yield, and provides better bonding and protection effects on flexible or curved materials.
Smart Images

Figure BDA0003451232940000061 
Figure BDA0003451232940000071 
Figure BDA0003451232940000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of UV anti-viscosity films, and in particular to an adhesive composition, a UV anti-viscosity adhesive and a UV anti-viscosity film. Background Art
[0002] When cutting and grinding optical glass and semiconductor materials during processing, a special protective film is needed to bond and fix them. After processing, the processed materials can be easily peeled off from the fixed film without affecting the material itself. UV anti-adhesive film is also known as UV adhesive tape, UV anti-adhesive tape, UV adhesive tape, UV anti-adhesive temporary bonding film. UV anti-adhesive film is a single-sided tape made of a special glue that is coated on a special film and shows high adhesion (2000gf / 25mm for SUS) in normal conditions, but the adhesion drops sharply after ultraviolet irradiation (10gf / 25mm for SUS).
[0003] UV anti-adhesive film has high adhesion when used for cutting, and can ensure that the material does not scatter, leave residual glue, prevent damage, and expand during cutting, grinding, and other processing. The UV irradiation reaction time is fast, ensuring the quality during the processing and effectively improving work efficiency. There is no residual glue or breakage when peeling off, ensuring the subsequent process, and it is anti-static and acid-alkali resistant.
[0004] However, when cutting flexible panels or many materials with large angles, irregular shapes or even curved surfaces, a UV anti-adhesion film with greater adhesion is needed to fix them, so as to avoid weak adhesion due to too little adhesion, which affects the process. Currently, the adhesion of UV anti-adhesion film is not strong (<2000gf / 25mm for SUS) and static electricity is generated during use, which can easily damage the processed materials and fall off during the process. There is also the problem of glue overflow, that is, as the bonding strength increases, the UV anti-adhesion film is more likely to overflow, and the overflowed glue is easy to adhere to the flexible panel, thereby affecting the process yield. Summary of the invention
[0005] The main purpose of the present invention is to provide an adhesive composition, a UV anti-viscosity adhesive and a UV anti-viscosity film, so as to solve the problems of serious adhesive overflow and low process yield of the UV anti-viscosity film in the prior art.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided an adhesive composition, which comprises, by mass percentage, 18 to 50 wt % of a curing resin, 40 to 80 wt % of a reactive diluent, 0.01 to 5 wt % of a photoinitiator, 0.01 to 5 wt % of a curing agent, and 0.01 to 40 wt % of a solvent; wherein the curing resin is a non-photosensitive resin, which includes, in addition to an epoxy resin, a hydroxyl-containing resin and / or a polyurethane resin, and the reactive diluent includes a photosensitive monomer.
[0007] Furthermore, the content of epoxy resin in the above-mentioned curing resin is 5-30%, and preferably the mass ratio of epoxy resin, hydroxyl-containing resin and polyurethane resin is 1:0.4-4:0.4-4.
[0008] Furthermore, the weight average molecular weight Mw of the above-mentioned epoxy resin is 5000-60000, and the epoxy resin is preferably selected from any one or more of bisphenol A epoxy resin, novolac epoxy resin, phenol novolac epoxy resin, o-cresol epoxy resin, and bisphenol F epoxy resin; and / or the weight average molecular weight Mw of the hydroxyl-containing resin is 3000-60000, and the hydroxyl-containing resin is preferably selected from any one or more of polyether polyol resin, polyester diol resin, alkyl diol resin, and diepoxy ethylene glycol bisglycidyl ether resin; and / or the weight average molecular weight Mw of the polyurethane resin is 5000-100000, and the polyurethane resin is preferably selected from any one or more of polyurethane epoxy resin, polyether polyurethane resin, and polyester polyurethane resin.
[0009] Furthermore, the mass ratio of the above-mentioned curing resin to the reactive diluent is 1:0.8-4, preferably the reactive diluent also includes a non-photosensitive monomer, and the content of the photosensitive monomer in the reactive diluent is 10-80wt%, preferably 15-65wt%, preferably the photosensitive monomer includes any one or more of a monofunctional monomer, a difunctional monomer and a multifunctional monomer, preferably the non-photosensitive monomer includes any one or more of a hydroxyl group-containing monomer and an epoxy group monomer.
[0010] Furthermore, the content of the above-mentioned photoinitiator is 0.05-3wt%, and the photoinitiator is preferably a free radical photoinitiator, and the free radical photoinitiator is preferably selected from any one or more of methyl benzoylformate, 1-hydroxycyclohexane benzophenone, benzil dimethyl ether, diphenylphosphine oxide, tetraethyl Michler's ketone, and fluorinated diphenyl titanocene.
[0011] Furthermore, the content of the above-mentioned curing agent is 0.5-2wt%, and the curing agent preferably includes an isocyanate curing agent, and the isocyanate curing agent is preferably selected from any one or more of toluene diisocyanate, diphenylmethane diisocyanate, aromatic polyisocyanate, and alicyclic polyisocyanate. The curing agent also preferably includes an amine curing agent, and the mass ratio of the isocyanate curing agent to the amine curing agent is preferably 1:0.01-0.4, and the amine curing agent is preferably selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine, and polyethylenepolyamine.
[0012] Furthermore, the above-mentioned viscose composition also includes 0.1 to 5 wt% of an antistatic agent, preferably 0.1 to 3%. Preferably, the antistatic agent is selected from any one or more of polythiophene derivatives, polyaniline derivatives, surface-modified single-walled or multi-walled carbon nanotubes, graphene or its derivatives, fullerenes, carbon black, lithium bis(trifluoromethanesulfonyl)imide, tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, and nanometal wires.
[0013] Furthermore, the content of the above-mentioned solvent is 10-30wt%, and the solvent is preferably selected from any one or more of ethyl acetate, butyl acetate, acetone, butanone, methyl isobutyl ketone, isopropanol, n-butanol, propylene glycol methyl ether, and toluene.
[0014] According to another aspect of the present invention, a UV viscosity-reducing adhesive is provided, which is prepared by mixing the components of an adhesive composition, and the adhesive composition is the above-mentioned adhesive composition.
[0015] According to another aspect of the present invention, a UV anti-viscosity film is provided, comprising a substrate film, a UV anti-viscosity adhesive and a release film covering layer stacked in sequence, wherein the UV anti-viscosity adhesive is the aforementioned UV anti-viscosity adhesive.
[0016] By applying the technical solution of the present invention, epoxy resin can increase the crosslinking density and improve the glass transition temperature Tg. The hydroxyl-containing resin has high adhesion and good flexibility, helps to improve viscosity and control coating properties. The polyurethane resin has high strength, helps to improve bonding strength, and has excellent weather resistance. The photosensitive monomer active diluent mainly dissolves and dilutes oligomers, adjusts the viscosity of the system, and most importantly, participates in the photocuring reaction. The above-mentioned types of curing resins and photosensitive monomers cooperate to make the UV viscosity-reducing adhesive simultaneously photocurable and thermally cured. By controlling its content within the above range and through the synergistic coordination of the other components, the UV viscosity-reducing adhesive has a suitable crosslinking density, hardness and viscosity, which helps to reduce the probability of overflow, reduce the difficulty of peeling during the process, and improve the process yield. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0018] As analyzed in the background technology, the UV anti-viscosity film in the prior art has the problems of serious glue overflow and low process yield. To solve this problem, the present invention provides an adhesive composition, a UV anti-viscosity adhesive and a UV anti-viscosity film.
[0019] In a typical embodiment of the present application, an adhesive composition is provided, which comprises, by mass percentage, 18 to 50 wt % of a curable resin, 40 to 80 wt % of a reactive diluent, 0.01 to 5 wt % of a photoinitiator, 0.01 to 5 wt % of a curing agent, and 0.01 to 40 wt % of a solvent; wherein the curable resin is a non-photosensitive resin, which includes, in addition to an epoxy resin, a hydroxyl-containing resin and / or a polyurethane resin, and the reactive diluent includes a photosensitive monomer.
[0020] Epoxy resin can increase the crosslinking density and raise the glass transition temperature Tg. Resins containing hydroxyl groups have high adhesion and good flexibility, which helps to increase viscosity and control coating properties. Polyurethane resin has high strength, which helps to increase bonding strength and has excellent weather resistance. Photosensitive monomer active diluents mainly dissolve and dilute oligomers, adjust the viscosity of the system, and most importantly, participate in the photocuring reaction. The above-mentioned types of curing resins and photosensitive monomers cooperate to make the UV viscosity-reducing adhesive simultaneously photocurable and thermally cured. By controlling its content within the above range and through the synergistic coordination of the other components, the UV viscosity-reducing adhesive has a suitable crosslinking density, hardness and viscosity, which helps to reduce the probability of overflow, reduce the difficulty of peeling during the process, and improve the process yield.
[0021] Epoxy resin can increase the cross-linking density and raise the glass transition temperature Tg. If too much is added, the bonding strength will be too high, which will affect the construction performance. If too little is added, the heat resistance of the adhesive will be affected. Preferably, the content of epoxy resin in the above-mentioned curing resin is 5 to 30%, such as the content of epoxy resin is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, etc.
[0022] The preferred mass ratio of epoxy resin, hydroxyl-containing resin and polyurethane resin is 1:0.4~4:0.4~4. Since the hydroxyl-containing resin has a large number of highly active hydroxyl groups, the polyurethane resin has excellent weather resistance and has high strength, adhesion and excellent flexibility. Controlling the ratio of the three resins within the above range helps to maximize the synergistic effect among the three.
[0023] In one embodiment of the present application, the weight average molecular weight Mw of the above-mentioned epoxy resin is 5000-60000, such as the weight average molecular weight Mw of the epoxy resin is 5000, 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, etc., and the epoxy resin is preferably selected from any one or more of bisphenol A epoxy resin, novolac epoxy resin, phenol novolac epoxy resin, o-cresol epoxy resin, and bisphenol F epoxy resin. In some embodiments of the present application, the weight average molecular weight Mw of the hydroxyl-containing resin is 3000-60000, such as the weight average molecular weight Mw of the hydroxyl-containing resin is 3000, 5000, 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, etc. Preferably, the hydroxyl-containing resin is selected from any one or more of polyether polyol resin, polyester diol resin, alkyl diol resin, and diethylene glycol diglycidyl ether resin. In some embodiments of the present application, the weight average molecular weight Mw of the polyurethane resin is 5000-100000, such as the weight average molecular weight Mw of the polyurethane resin is 5000, 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000, 60000, 70000, 80000, 90000, 100000, etc. Preferably, the polyurethane resin is selected from any one or more of polyurethane epoxy resin, polyether polyurethane resin, and polyester polyurethane resin.
[0024] The preferred type and molecular weight of the curing resin is more helpful to control the viscosity of the UV adhesive and balance the adhesion, crosslinking density, flexibility, hardness and strength of the UV adhesive, so that it can be easily prepared and coated, which helps to reduce the probability of overflow, reduce the difficulty of peeling during the process, and improve the process yield; and make the adhesive composition have excellent heat resistance, further meeting the use of the flexible panel process. Among them, the smaller the side chain group in the polyester polyurethane resin and the polyether polyurethane resin, the more methylene groups between the ether bonds or ester bonds, and the higher the molecular weight of the crystalline soft segment, so that the polyurethane resin has higher crystallinity and greater bonding strength.
[0025] In one embodiment of the present application, the mass ratio of the above-mentioned curing resin to the reactive diluent is 1:0.8-4, preferably the reactive diluent also includes a non-photosensitive monomer, and the content of the photosensitive monomer in the reactive diluent is 10-80wt%, preferably 15-65wt%, preferably the photosensitive monomer includes any one or more of a monofunctional monomer, a difunctional monomer and a multifunctional monomer, preferably the non-photosensitive monomer includes any one or more of a hydroxyl group-containing monomer and an epoxy group monomer.
[0026] Photosensitive monomer active diluents mainly dissolve and dilute oligomers, adjust the viscosity of the system, and most importantly participate in the photocuring reaction. If the content is too low, the crosslinking degree will be insufficient, and there will be problems with low curing speed and adhesion. Adding too much can easily reduce the viscosity of the UV anti-viscosity adhesive, affecting the coating. The photocuring speed is fast, the crosslinking density after curing is large, and the hardness and brittleness of the reaction adhesive layer after curing are high, which is not conducive to improving the bonding strength, thereby limiting its application in the process of flexible or curved components. Therefore, it is preferred that the photosensitive monomer is matched with a non-photosensitive monomer, mainly to increase the molecular weight and improve the adhesion, thereby helping to improve the bonding strength of the UV anti-viscosity adhesive and expand its application in the process of flexible or curved components. Combined with the synergistic combination effect of the curing resin or photosensitive monomer structure, it is preferred that the monofunctional monomer is selected from any one or more of hydroxyethyl methacrylate, ethoxyethyl acrylate, ethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, butyl acrylate, methyl methacrylate, acrylic acid, diisooctyl maleate, and monomers containing functional functional groups. Preferably, the monomer containing functional groups is selected from any one or more of ethoxylated neopentyl glycol methoxy monoacrylate, 1,6-hexanediol methoxy monoacrylate, ethoxyethoxyethyl acrylate, and methoxyethyl acrylate, and more preferably, a combination of hydroxyethyl methacrylate and methyl methacrylate. If the amount of monofunctional monomer added is too much, the adhesive layer after curing will be soft, and if the amount of added is too little, the adhesive layer after curing will be too hard. Therefore, the content of the monofunctional monomer in the photosensitive monomer is preferably 20 to 40 wt%.
[0027] In order to further improve the synergistic effect of the difunctional monomer and the multifunctional monomer with the monofunctional monomer, the difunctional monomer is preferably selected from any one or more of tripropylene glycol diacrylate, dipropylene glycol diacrylate, hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol divinyl ether, and ethoxylated bisphenol A epoxy acrylate, and the multifunctional monomer is preferably selected from any one or more of trimethylolpropane triacrylate, pentaerythritol triacrylate, ditrihydroxymethylpropane tetraacrylate, and dipentaerythritol penta / hexaacrylate, and further preferably one or a combination of two of dipentaerythritol penta / hexaacrylate. If too much difunctional and multifunctional monomers are added, the reaction adhesive layer will be harder after curing, which is not conducive to improving the bonding strength and limits its application in the process of flexible or curved components. Therefore, the content of the difunctional monomer is preferably 10-20wt%, and the content of the multifunctional monomer is preferably 5-15wt%. The non-photosensitive monomer is preferably selected from any one or more of diepoxy ethylene glycol diglycidyl ether, polyester diol, polyether diol, and alkyl diol, so as to take into account the peel strength of the UV anti-viscosity film before and after UV irradiation.
[0028] After being irradiated by ultraviolet light, the photoinitiator absorbs the energy of light and splits into multiple active free radicals, which trigger a chain polymerization reaction between the photocurable resin and the active diluent, causing the UV viscosity-reducing adhesive to crosslink and cure. If too much photoinitiator is added, the coating surface will absorb too much ultraviolet light to initiate, which will weaken the penetration of ultraviolet light, resulting in incomplete curing of the bottom layer. The peel strength of the UV viscosity-reducing film will be too high after UV irradiation, and there will be problems with residual glue and storage thermal stability, which is not conducive to improving the process yield; when the amount of photoinitiator added is too little, it is not conducive to the complete reaction of the photocurable resin and the active diluent, and it is still easy to cause the peel strength of the UV viscosity-reducing film to be too high after UV irradiation, and there will be residual glue, which is not conducive to improving the process yield. Therefore, the content of the above-mentioned photoinitiator is preferably 0.05-3wt%, such as the preferred photoinitiator content of the present application is 0.5wt%, 1wt%, 1.5wt%, 2wt%, 3wt%, etc. The preferred photoinitiator is a free radical photoinitiator, and the preferred free radical photoinitiator is selected from any one or more of methyl benzoylformate, 1-hydroxycyclohexane benzophenone, benzil dimethyl ether, diphenylphosphine oxide, tetraethyl Michler's ketone, and fluorinated diphenyl titanocene.
[0029] Adding too much curing agent will cause the thermosetting resin to react completely, which is not conducive to reducing the peel strength before UV irradiation. Adding too little curing agent will cause the curing resin to react too little, resulting in excessive peel strength. At the same time, the peel strength after UV irradiation will be too high and there will be residual glue problems. In order to take into account the peel strength before and after UV irradiation, the content of the above-mentioned curing agent is preferably 0.5-2wt%. For example, the preferred curing agent content of the present application is 0.5wt%, 0.51wt%, 1wt%, 1.5wt%, 2wt%, etc.
[0030] The curing agent includes an isocyanate curing agent, and the isocyanate curing agent is preferably selected from any one or more of toluene diisocyanate, diphenylmethane diisocyanate, aromatic polyisocyanate, and alicyclic polyisocyanate. Further, the isocyanate curing agent is preferably selected from any one or more of Coronate LS, 2037, Desmodur L-75, Takenate D-101E, Risheng SC-75LT, and Wanhua Chemical TL-75E. The isocyanate curing agent contains a highly unsaturated structure of an isocyanate group (-NCO), which determines that it has a high reactivity. The curing agent reacts with the epoxy group in the epoxy resin to generate a hydroxyl group, and the hydroxyl group reacts with the isocyanate again, and at the same time includes a reaction between the isocyanate and the polyol and its small molecule alcohol, so as to be more conducive to exerting its curing performance.
[0031] In some embodiments, the curing agent preferably further comprises an amine curing agent, and the mass ratio of the isocyanate curing agent to the amine curing agent is preferably 1:0.01-0.4, and the amine curing agent is preferably selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine, and polyethylenepolyamine. Among them, the isocyanate curing agent is used in combination with the amine curing agent, and the amine ions in the amine curing agent can also react with the epoxy group and isocyanate in the epoxy resin, thereby further improving the curing efficiency of the cured resin.
[0032] In order to reduce the influence of static electricity on the workpiece and improve the process yield, the above-mentioned adhesive composition preferably also includes 0.1-5wt% of an antistatic agent, such as the content of the antistatic agent in the present application is preferably 0.1wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.9wt%, 5wt%, etc., preferably 0.1-3%, such as the content of the antistatic agent in the present application is preferably 0.1wt%, 0.5wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, etc., and the antistatic agent is preferably selected from any one or more of polythiophene derivatives, polyaniline derivatives, surface modified single-walled or multi-walled carbon nanotubes, graphene or its derivatives, fullerenes, carbon black, lithium bis(trifluoromethanesulfonyl)imide, tributylmethylammonium bis(trifluoromethanesulfonyl)imide salt, and nanometal wires.
[0033] In one embodiment of the present application, the content of the above-mentioned solvent is 10-30wt%, and the preferred solvent is selected from any one or more of ethyl acetate, butyl acetate, acetone, butanone, methyl isobutyl ketone, isopropanol, n-butanol, propylene glycol methyl ether, and toluene.
[0034] The solvent can adjust the viscosity of the adhesive composition, so that the difficulty of coating will not be increased due to excessive viscosity, nor will it be impossible to coat a thicker adhesive layer due to too low viscosity, and at the same time, the baking time after coating will be long, thereby reducing the production efficiency. For example, the preferred solvent content in the present application is 0.1wt%, 1.88wt%, 5.5wt%, 10wt%, 15wt%, 17.49wt%, 18.09wt%, 18.49wt%, 20wt%, 22.45wt%, 25wt%, 27wt%, 30wt%, 35wt%, 40wt%, etc., and further, it is preferably 10wt%, 15wt%, 17.49wt%, 18.09wt%, 18.49wt%, 20wt%, 22.45wt%, 25wt%, 27wt%, 30wt%, etc.
[0035] In another typical embodiment of the present application, a UV viscosity-reducing adhesive is provided, which is prepared by mixing the components of an adhesive composition, and the adhesive composition is the above-mentioned adhesive composition.
[0036] By controlling the content of each component in the adhesive composition within the above range and through the synergistic coordination of the remaining components, the UV viscosity-reducing adhesive has a suitable cross-linking density, hardness and viscosity, which helps to reduce the probability of glue overflow. And the UV viscosity-reducing film including the UV viscosity-reducing adhesive of the present application has high adhesion and acid and alkali resistance when used for cutting, and ensures that the material does not fly, does not have residual glue, does not expand, and prevents damage during cutting, grinding and other processing. Even on flexible panels or many shapes with large angles, irregular or even curved surfaces, it protects, fixes and supports flexible or curved surfaces. The UV irradiation reaction time is fast, which ensures the quality during the processing and effectively improves work efficiency. There is no residual glue or broken glue when peeling, which reduces the peeling force in the process, improves the process yield, and ensures the subsequent process.
[0037] In another typical embodiment of the present application, a UV anti-viscosity film is provided, comprising a substrate film, a UV anti-viscosity adhesive and a release film covering layer stacked in sequence, wherein the UV anti-viscosity adhesive is the aforementioned UV anti-viscosity adhesive.
[0038] The UV anti-viscosity film including the above-mentioned UV anti-viscosity adhesive of the present application reduces the peeling force in the process, improves the process yield, and ensures the subsequent processes.
[0039] Among them, the preferred preparation method of the UV anti-viscosity film comprises: adding a curing resin, an active diluent, an antistatic agent and a solvent into a reaction kettle and mechanically stirring at a uniform speed for 1 to 3 hours to obtain a main agent A.
[0040] Under yellow light or in dark, add photoinitiator to main agent A in proportion and stir mechanically for 15 to 60 minutes, then add curing agent and stir mechanically for 15 to 60 minutes to obtain antistatic UV anti-viscosity adhesive, wherein the addition ratio of each component refers to the corresponding ratio in the adhesive composition; finally, apply it on 50 μm thick PET, PO and PVC substrates by scraping or slit coating machine, put it into 80 to 110 ° C oven for 1 to 5 minutes after coating, and the thickness of the adhesive film after drying is about 10 to 30 μm, then use flat film laminating machine to attach release film, select PET light release film release surface to attach to the dried UV anti-viscosity adhesive, and finally obtain UV anti-viscosity film.
[0041] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0042] Example 1
[0043] The composition of the viscose composition of Example 1 is shown in Table 1.
[0044] Table 1
[0045]
[0046]
[0047] Example 2
[0048] The difference between Example 2 and Example 1 is that:
[0049] The content of bisphenol A type epoxy resin: E-20 (601) is 12 wt %, the content of hydroxyl-containing resin VORANOL 3003N is 18 wt %, and the content of ethyl acetate is 8.09 wt %, to obtain an adhesive composition.
[0050] Example 3
[0051] The difference between Example 3 and Example 2 is that:
[0052] The content of bisphenol A epoxy resin E-20 (601) was 7.41 wt %, the content of hydroxyl-containing resin VORANOL 3003N was 2.96 wt %, and the content of polyether polyurethane resin Mw=60000 was 29.63 wt %, to obtain an adhesive composition.
[0053] Example 4
[0054] The difference between Example 4 and Example 2 is that:
[0055] The content of bisphenol A epoxy resin E-20 (601) was 7.41 wt %, the content of hydroxyl-containing resin VORANOL 3003N was 29.63 wt %, and the content of polyether polyurethane resin Mw=60000 was 2.96 wt %, to obtain an adhesive composition.
[0056] Example 5
[0057] The difference between Example 5 and Example 2 is that:
[0058] The content of bisphenol A epoxy resin E-20 (601) is 12 wt %, the content of hydroxyl-containing resin VORANOL 3003N is 26 wt %, and the content of polyether polyurethane resin Mw=60000 is 2 wt %, to obtain an adhesive composition.
[0059] Example 6
[0060] The difference between Example 6 and Example 2 is that the content of bisphenol A epoxy resin E-20 (601) is 14.68wt%, the content of hydroxyl-containing resin VORANOL 3003N is 22.02wt%, and the content of polyether polyurethane resin Mw=60000 is 12.19wt%;
[0061] The content of hydroxyethyl methacrylate is 10.3 wt %, the content of tripropylene glycol diacrylate is 10.3 wt %, the content of dipentaerythritol hexaacrylate is 10.3 wt %, and the content of diepoxy ethylene glycol bisglycidyl ether is 8.21 wt %, to obtain an adhesive composition.
[0062] Example 7
[0063] The difference between Example 7 and Example 2 is that the content of bisphenol A epoxy resin E-20 (601) is 5.29wt%, the content of hydroxyl-containing resin VORANOL 3003N is 7.93wt%, and the content of polyether polyurethane resin Mw=60000 is 4.39wt%;
[0064] The content of hydroxyethyl methacrylate is 18.54 wt %, the content of tripropylene glycol diacrylate is 18.54 wt %, the content of dipentaerythritol hexaacrylate is 18.54 wt %, and the content of diepoxyethylene glycol bisglycidyl ether is 14.78 wt %, to obtain an adhesive composition.
[0065] Example 8
[0066] The difference between Example 8 and Example 2 is that the content of bisphenol A epoxy resin E-20 (601) is 17.63wt%, the content of hydroxyl-containing resin VORANOL 3003N is 26.44wt%, and the content of polyether polyurethane resin Mw=60000 is 14.63wt%;
[0067] The content of hydroxyethyl methacrylate is 7.72 wt %, the content of tripropylene glycol diacrylate is 7.72 wt %, the content of dipentaerythritol hexaacrylate is 7.72 wt %, and the content of diepoxyethylene glycol bisglycidyl ether is 6.15 wt %, to obtain an adhesive composition.
[0068] Example 9
[0069] The difference between Example 9 and Example 2 is that the content of hydroxyethyl methacrylate is 2.4wt%, the content of tripropylene glycol diacrylate is 2.4wt%, the content of dipentaerythritol hexaacrylate is 2.4wt%, and the content of diepoxyethylene glycol diglycidyl ether is 40.8wt%, to obtain a viscose composition.
[0070] Example 10
[0071] The difference between Example 10 and Example 2 is that the content of hydroxyethyl methacrylate is 4.8wt%, the content of tripropylene glycol diacrylate is 4.8wt%, the content of dipentaerythritol hexaacrylate is 4.8wt%, and the content of diepoxyethylene glycol diglycidyl ether is 33.6wt%, to obtain a viscose composition.
[0072] Embodiment 11
[0073] The difference between Example 11 and Example 2 is that the content of hydroxyethyl methacrylate is 10.4wt%, the content of tripropylene glycol diacrylate is 10.4wt%, the content of dipentaerythritol hexaacrylate is 10.4wt%, and the content of diepoxyethylene glycol diglycidyl ether is 16.8wt%, to obtain a viscose composition.
[0074] Example 12
[0075] The difference between Example 12 and Example 2 is that the content of hydroxyethyl methacrylate is 1.6wt%, the content of tripropylene glycol diacrylate is 1.6wt%, the content of dipentaerythritol hexaacrylate is 1.6wt%, and the content of diepoxyethylene glycol diglycidyl ether is 43.2wt%, to obtain a viscose composition.
[0076] Embodiment 13
[0077] The difference between Example 13 and Example 2 is that the content of toluene diisocyanate is 0.406 wt %, and the content of diethylenetriamine is 0.004 wt %, to obtain a viscose composition.
[0078] Embodiment 14
[0079] The difference between Example 14 and Example 2 is that the content of toluene diisocyanate is 0.293 wt %, and the content of diethylenetriamine is 0.117 wt %, to obtain a viscose composition.
[0080] Embodiment 15
[0081] The difference between Example 15 and Example 2 is that the content of toluene diisocyanate is 0.082 wt %, and the content of diethylenetriamine is 0.041 wt %, to obtain a viscose composition.
[0082] Example 16
[0083] The difference between Example 16 and Example 2 is that the epoxy resin is a phenolic epoxy resin, Kunshan Guodu Chemical YDPN-638-1, with a Mw of 5000, and an adhesive composition is obtained.
[0084] Embodiment 17
[0085] The difference between Example 17 and Example 2 is that the epoxy resin is a phenolic epoxy resin, Kunshan Guodu Chemical YDPN-638-3, with a Mw of 60,000, and an adhesive composition is obtained.
[0086] Embodiment 18
[0087] The difference between Example 18 and Example 2 is that the epoxy resin is a phenolic epoxy resin, Kunshan Guodu Chemical YDPN-638-2, with a Mw of 3000, and an adhesive composition is obtained.
[0088] Embodiment 19
[0089] The difference between Example 19 and Example 2 is that the hydroxyl-containing resin is Evonik LH818-05N with a Mw of 60,000, and a viscose composition is obtained.
[0090] Embodiment 20
[0091] The difference between Example 20 and Example 2 is that the hydroxyl-containing resin is SANNIX PP-3000 with a Mw of 3000, and an adhesive composition is obtained.
[0092] Embodiment 21
[0093] The difference between Example 21 and Example 2 is that the hydroxyl-containing resin is SANNIX PP-2000 with a Mw of 2000, and an adhesive composition is obtained.
[0094] Embodiment 22
[0095] The difference between Example 22 and Example 2 is that the polyurethane resin is Showa ELX5190 with a Mw of 100,000, and an adhesive composition is obtained.
[0096] Embodiment 23
[0097] The difference between Example 23 and Example 2 is that the polyurethane resin is Sartomer CN9010NS with a Mw of 5800, and an adhesive composition is obtained.
[0098] Embodiment 24
[0099] The difference between Example 24 and Example 2 is that the polyurethane resin is Changxing DR-U110 with a Mw of 3000, and a viscose composition is obtained.
[0100] Embodiment 25
[0101] The difference between Example 25 and Example 2 is that the curing resin is 6 wt% of a hydroxyl-containing resin: VORANOL 3003N, 6 wt% of a bisphenol A type epoxy resin: E-20 (601), and 6 wt% of a polyether type polyurethane resin: Mw = 60000;
[0102] The photosensitive monomer is 16 wt % of hydroxyethyl methacrylate, 4 wt % of tripropylene glycol diacrylate, and 20 wt % of dipentaerythritol hexaacrylate; the non-photosensitive monomer is 40 wt % of diepoxy ethylene glycol diglycidyl ether;
[0103] The solvent is 1.88 wt% ethyl acetate;
[0104] The antistatic agent is 0.1wt% of lithium bis(trifluoromethanesulfonyl)imide LiTFSI;
[0105] The photoinitiator is 0.01 wt% of benzil dimethyl ether (651);
[0106] The curing agent is 0.00975 wt % of toluene diisocyanate and 0.00025 wt % of diethylenetriamine to obtain an adhesive composition.
[0107] Embodiment 26
[0108] The difference between Example 26 and Example 2 is that the curing resin is 20 wt% of a hydroxyl-containing resin: VORANOL 3003N, 10 wt% of a bisphenol A type epoxy resin: E-20 (601), and 30 wt% of a polyether type polyurethane resin: Mw = 60000;
[0109] The photosensitive monomer is 10wt% of hydroxyethyl methacrylate, 5wt% of tripropylene glycol diacrylate, and 5wt% of dipentaerythritol hexaacrylate; the non-photosensitive monomer is 20wt% of diepoxy ethylene glycol diglycidyl ether;
[0110] The solvent is 0.1wt% ethyl acetate;
[0111] The antistatic agent is 4.9 wt% of lithium bis(trifluoromethanesulfonyl)imide LiTFSI;
[0112] The photoinitiator is 3 wt% of benzil dimethyl ether (651);
[0113] The curing agent is 1.95 wt % of toluene diisocyanate and 0.05 wt % of diethylenetriamine to obtain an adhesive composition.
[0114] Embodiment 27
[0115] The difference between Example 27 and Example 2 is that the curing resin is 6 wt% of a hydroxyl-containing resin: VORANOL 3003N, 6 wt% of a bisphenol A type epoxy resin: E-20 (601), and 6 wt% of a polyether type polyurethane resin: Mw = 60000;
[0116] The photosensitive monomer is 10wt% of hydroxyethyl methacrylate, 5wt% of tripropylene glycol diacrylate, and 5wt% of dipentaerythritol hexaacrylate; the non-photosensitive monomer is 20wt% of diepoxy ethylene glycol diglycidyl ether;
[0117] The solvent is 40wt% ethyl acetate;
[0118] The antistatic agent is 0.5wt% of lithium bis(trifluoromethanesulfonyl)imide LiTFSI;
[0119] The photoinitiator is 1 wt% of benzil dimethyl ether (651);
[0120] The curing agent is 0.49 wt % of toluene diisocyanate and 0.01 wt % of diethylenetriamine to obtain an adhesive composition.
[0121] Embodiment 28
[0122] The difference between Example 28 and Example 2 is that the curing resin is 6 wt% of a hydroxyl-containing resin: VORANOL 3003N, 6 wt% of a bisphenol A type epoxy resin: E-20 (601), and 6 wt% of a polyether type polyurethane resin: Mw = 60000;
[0123] The photosensitive monomer is 5wt% of hydroxyethyl methacrylate, 5wt% of tripropylene glycol diacrylate, and 10wt% of dipentaerythritol hexaacrylate; the non-photosensitive monomer is 20wt% of diepoxy ethylene glycol diglycidyl ether;
[0124] The solvent is 27 wt% ethyl acetate;
[0125] The antistatic agent is 5wt% of lithium bis(trifluoromethanesulfonyl)imide LiTFSI;
[0126] The photoinitiator is 5 wt% of benzil dimethyl ether (651);
[0127] The curing agent is 4.9 wt % of toluene diisocyanate and 0.1 wt % of diethylenetriamine to obtain an adhesive composition.
[0128] The composition of the viscose composition of Example 29 is shown in Table 2, the composition of the viscose composition of Example 30 is shown in Table 3, the composition of the viscose composition of Example 31 is shown in Table 4, the composition of the viscose composition of Example 32 is shown in Table 5, the composition of the viscose composition of Example 33 is shown in Table 6, the composition of the viscose composition of Comparative Example 1 is shown in Table 7, the composition of the viscose composition of Comparative Example 2 is shown in Table 8, and the composition of the viscose composition of Comparative Example 3 is shown in Table 9.
[0129] Table 2
[0130]
[0131] Table 3
[0132]
[0133]
[0134] Table 4
[0135]
[0136] Table 5
[0137]
[0138]
[0139] Table 6
[0140]
[0141] Table 7
[0142]
[0143]
[0144] Table 8
[0145]
[0146] Table 9
[0147]
[0148] Prepare UV anti-viscosity film according to the following method:
[0149] The curing resin, active diluent, antistatic agent and solvent were added into a reaction kettle and mechanically stirred at a constant speed for 2 hours to obtain the main agent A.
[0150] Under yellow light or in dark, add photoinitiator to main agent A in proportion and stir mechanically for 30 minutes, then add curing agent and stir mechanically for 30 minutes to obtain antistatic UV anti-viscosity adhesive, wherein the addition ratio of each component refers to the corresponding ratio in the adhesive composition of Examples 1 to 33 and Comparative Examples 1 to 3 respectively; finally, use a coating machine to scrape or a slit coating machine to coat on 50 μm thick PET, PO and PVC substrates respectively, put it into a 100°C oven for baking for 3 minutes after coating, and the thickness of the adhesive film after drying is about 20 μm, then use a flat film laminating machine to attach a release film, select the release surface of the PET light release film and attach it to the dried UV anti-viscosity adhesive, and finally obtain a UV anti-viscosity film.
[0151] Peel strength test:
[0152] The UV anti-adhesion films prepared above were cut into 25 mm wide and 150 mm long, and the release films were removed and attached to stainless steel plates (SUS), PET and glass substrates respectively. They were pressed 6 times with a 2kg roller respectively. At room temperature, the pre-UV peel strength was tested with Instron 34SC1. The post-UV peel strength was tested with Tobo 8203S after standing under yellow light for 20 minutes.
[0153] Reliability test:
[0154] The UV anti-adhesion films prepared above were cut into 25 mm wide and 150 mm long, and the release films were removed and attached to stainless steel plates (SUS), PET and glass substrates respectively. They were pressed 6 times with a 2kg roller, and the pre-UV peel strength was tested with Instron 34SC1 at 85°C and RH85%. The post-UV peel strength was tested with Tobo 8203S after standing under yellow light for 240 hours in the same way.
[0155] Resistance test:
[0156] The surface resistance was measured using a SIMCO ST-4 surface resistance meter.
[0157] The test requirements for peel strength at room temperature, the test requirements at 85°C and RH85% (standing for 240 hours), and the test requirements for resistance are shown in Table 10. The test results for peel strength at room temperature are listed in Table 11, and the test results at 85°C and RH85% (standing for 240 hours) are listed in Table 12.
[0158] Table 10
[0159]
[0160] Table 11
[0161]
[0162]
[0163]
[0164] Table 12
[0165]
[0166]
[0167] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0168] Epoxy resin can increase the crosslinking density and raise the glass transition temperature Tg. Resins containing hydroxyl groups have high adhesion and good flexibility, which helps to increase viscosity and control coating properties. Polyurethane resin has high strength, which helps to increase bonding strength and has excellent weather resistance. Photosensitive monomer active diluents mainly dissolve and dilute oligomers, adjust the viscosity of the system, and most importantly, participate in the photocuring reaction. The above-mentioned types of curing resins and photosensitive monomers cooperate to make the UV viscosity-reducing adhesive simultaneously photocurable and thermally cured. By controlling its content within the above range and through the synergistic coordination of the other components, the UV viscosity-reducing adhesive has a suitable crosslinking density, hardness and viscosity, which helps to reduce the probability of overflow, reduce the difficulty of peeling during the process, and improve the process yield.
[0169] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A viscose composition, characterized in that: In terms of mass percentage, the viscose composition comprises: 18-50wt% of curing resin; 40-80wt% of active diluent; 0.01-5wt% of photoinitiator; 0.01 to 5 wt% of a curing agent; 0.01-40 wt % of solvent; Wherein, the curing resin is a non-photosensitive resin, and the non-photosensitive resin includes, in addition to epoxy resin, a hydroxyl-containing resin and / or a polyurethane resin, and the reactive diluent includes a photosensitive monomer; The content of the epoxy resin in the curing resin is 5 to 30%; The weight average molecular weight Mw of the epoxy resin is 5000-60000.
2. The viscose composition according to claim 1, characterized in that: The mass ratio of the epoxy resin, the hydroxyl-containing resin and the polyurethane resin is 1:0.4-4:0.4-4.
3. The viscose composition according to claim 1 or 2, characterized in that: The epoxy resin is selected from any one or more of bisphenol A epoxy resin, novolac epoxy resin, phenol novolac epoxy resin, o-cresol novolac epoxy resin, and bisphenol F epoxy resin; and / or the weight average molecular weight Mw of the hydroxyl-containing resin is 3000 to 60000; And / or the weight average molecular weight Mw of the polyurethane resin is 5,000 to 100,000.
4. The viscose composition according to claim 1 or 2, characterized in that: The hydroxyl-containing resin is selected from any one or more of polyether polyol resin, polyester diol resin, alkyl diol resin, and diepoxy ethylene glycol bisglycidyl ether resin.
5. The viscose composition according to claim 1 or 2, characterized in that: The polyurethane resin is selected from any one or more of polyurethane epoxy resin, polyether polyurethane resin and polyester polyurethane resin.
6. The viscose composition according to claim 1 or 2, characterized in that: The mass ratio of the curing resin to the active diluent is 1:0.8-4.
7. The viscose composition according to claim 1 or 2, characterized in that: The reactive diluent further comprises a non-photosensitive monomer, and the content of the photosensitive monomer in the reactive diluent is 10 to 80 wt %.
8. The viscose composition according to claim 7, characterized in that: The content of the photosensitive monomer in the reactive diluent is 15 to 65 wt %.
9. The viscose composition according to claim 1 or 2, characterized in that: The photosensitive monomer includes any one or more of a monofunctional monomer, a difunctional monomer and a multifunctional monomer.
10. The viscose composition according to claim 8, characterized in that: The non-photosensitive monomer includes any one or more of a monomer containing a hydroxyl group and a monomer containing an epoxy group.
11. The viscose composition according to claim 1, characterized in that: The content of the photoinitiator is 0.05-3 wt %.
12. The viscose composition according to claim 1, characterized in that: The photoinitiator is a free radical photoinitiator.
13. The adhesive composition according to claim 12, characterized in that: The free radical photoinitiator is selected from any one or more of methyl benzoylformate, 1-hydroxycyclohexane benzophenone, benzil dimethyl ether, diphenylphosphine oxide, tetraethyl Michler's ketone, and fluorinated diphenyl titanocene.
14. The viscose composition according to claim 1, characterized in that: The content of the curing agent is 0.5-2wt%.
15. The viscose composition according to claim 1, characterized in that: The curing agent includes an isocyanate curing agent.
16. The adhesive composition according to claim 15, characterized in that: The isocyanate curing agent is selected from any one or more of toluene diisocyanate, diphenylmethane diisocyanate, aromatic polyisocyanate, and alicyclic polyisocyanate.
17. The viscose composition according to claim 15, characterized in that: The curing agent also includes an amine curing agent.
18. The adhesive composition according to claim 17, characterized in that: The mass ratio of the isocyanate curing agent to the amine curing agent is 1:0.01-0.
4.
19. The adhesive composition according to claim 17, characterized in that: The amine curing agent is selected from any one or more of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, hexamethylenediamine and polyethylenepolyamine.
20. The viscose composition according to claim 1, characterized in that: The adhesive composition further comprises 0.1 to 5 wt % of an antistatic agent.
21. The adhesive composition according to claim 20, characterized in that: The adhesive composition further comprises 0.1 to 3 wt % of an antistatic agent.
22. The adhesive composition according to claim 20, characterized in that: The antistatic agent is selected from any one or more of polythiophene derivatives, polyaniline derivatives, surface modified single-walled or multi-walled carbon nanotubes, graphene or its derivatives, fullerenes, carbon black, lithium bis(trifluoromethanesulfonylimide), tributylmethylammonium bis(trifluoromethanesulfonylimide) salt, and nanometal wires.
23. The viscose composition according to claim 1, characterized in that: The content of the solvent is 10-30 wt %.
24. The viscose composition according to claim 1, characterized in that: The solvent is selected from any one or more of ethyl acetate, butyl acetate, acetone, butanone, methyl isobutyl ketone, isopropanol, n-butanol, propylene glycol methyl ether and toluene.
25. A UV viscosity-reducing adhesive, prepared by mixing the components of an adhesive composition, characterized in that: The viscose composition is the viscose composition according to any one of claims 1 to 24.
26. A UV anti-viscosity film, comprising a substrate film, a UV anti-viscosity adhesive and a release film covering layer stacked in sequence, characterized in that: The UV viscosity-reducing adhesive is the UV viscosity-reducing adhesive as claimed in claim 25.
Citation Information
Patent Citations
Ultraviolet curing removable adhesive composition and adhesive sheet using the same
CN102177214A
UV viscosity-reduced glue and application thereof
CN109762509A